CORRECTION TREATMENT OF CHRONIC HEART FAILURE IN POSTINFARCTION PATIENTS - Деніна, Р. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
160 patients with heart failure classes II and III in postinfarction patients have undergone treatment by means of cardioprotector – isosorbide mononitrate – mononitrosid and metabolitotropic drug 5-lipoxygenase inhibitor corvitin/quercetin. All the suggested treatment regimens of heart failure in postinfarction patients had high antagonistic effectiveness, resulted in the decrease of blood pressure, pulse pressure, improved structural and functional characteristics of the myocardium (including the increase in ejection fraction (EF), and significant decrease of left ventricular end-diastolic dimension (LVEDd), end-diastolic volume (EDV), left ventricular mass index (LVMI), reduced NT-proBNP levels, Total NO and improved heart rate variability.